The yeast tRNA: pseudouridine synthase Pus1p displays a multisite substrate specificity - Motorin, Yuri; Keith, G.; Simon, C.; Foiret, D.; Simos, Geōrgios; Hurt, Ed; Grosjean, H. (RNA, 1998)
We have previously shown that the yeast gene PUS1 codes for a tRNA:pseudouridine synthase and that recombinant Pus1p catalyzes, in an intron-dependent way, the formation of Ψ34 and Ψ36 in the anticodon loop of the yeast minor tRNAIle in vitro (Simos G et al., 1996, EMBO J 15:2270-2284). Using a set of T7 transcripts of different tRNA genes, we now demonstrate that yeast pseudouridine synthase 1 catalyzes in vitro pseudouridine formation at positions 27 and/or 28 in several yeast cytoplasmic tRNAs and at position 35 in the intron-containing tRNATyr (anticodon GUA). Thus, Pus1p not only displays a broad specificity toward the RNA substrates, but is also capable of catalyzing the pseudouridine (Ψ) formation at distinct noncontiguous sites within the same tRNA molecule. The cell-free extract prepared from the yeast strain bearing disrupted gene PUS1 is unable to catalyze the formation of Ψ27, Ψ28, Ψ34, and Ψ36 in vitro, however, Ψ35 formation in the intron-containing tRNATyr(GUA) remains unaffected. Thus, in yeast, only one gene product accounts for tRNA pseudouridylation at positions 27, 28, 34, and 36, whereas for position 35 in tRNATyr, another site-specific tRNA:pseudouridine synthase with overlapping specificity exists. Mapping of pseudouridine residues present in various tRNAs extracted from the PUS1-disrupted strain confirms the in vitro data obtained with the recombinant Pus1p. In addition, they suggest that Pus1p is implicated in modification at positions U26, U65, and U67 in vivo.